Low-temperature fast-firing slurry containing lithium-containing tailings and ceramic bathroom high-pressure grouting product thereof
By introducing raw materials such as lithium tailings and magnesia into sanitary ceramic slurry and optimizing the formula, the problem of low utilization value of lithium tailings was solved, and low-temperature rapid firing of sanitary ceramic blanks and improved production efficiency were achieved.
Patent Information
- Application Number
- CN202411042113.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-31
AI Technical Summary
In existing technologies, lithium tailings have low utilization value and it is difficult to achieve low-temperature rapid firing of sanitary ceramic blanks, resulting in high production costs and low efficiency.
Low-temperature rapid-fired slurry containing lithium tailings is used. By introducing lithium tailings and magnesia clay to replace high-temperature materials such as potassium sodium feldspar, the slurry formula is optimized, the firing temperature is reduced, and high-temperature sand is used to achieve low-temperature rapid firing of high-pressure grouting products.
This technology enables low-temperature rapid firing of sanitary ceramic products, reducing production costs, improving production efficiency, and stabilizing the firing quality of the ceramic body.
Smart Images

Figure BDA0004972648700000081 
Figure BDA0004972648700000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of sanitary ceramics technology, and in particular to a low-temperature rapid-firing slurry containing lithium tailings and its high-pressure injection grouting products for ceramic sanitary ware. Background Technology
[0002] Lithium tailings, as industrial waste generated during lithium material production, are closely related to the rapid development of the lithium materials industry. For every ton of lithium carbonate produced, eight to ten tons of lithium tailings are generated. With the surge in market demand for lithium materials, the output of lithium tailings has been increasing year by year. However, lithium tailings themselves have low utilization value and are forced to be stockpiled due to difficulties in effective utilization. This disposal method not only occupies a large amount of land resources but also poses a potential threat to the ecological environment.
[0003] Toilet bases in sanitary ware ceramics are generally classified into two types based on their manufacturing process: traditional slip-casting products and high-pressure slip-casting products. Both types include single-sided and double-sided slip-casting structures, with double-sided slip-casting structures accounting for over 80% of high-pressure slip-casting products. Compared to single-sided slip-casting structures, double-sided slip-casting structures have lower firing requirements for the ceramic body. Therefore, ceramic sanitary ware products based on high-pressure slip-casting technology provide conditions for low-temperature, rapid firing of the ceramic body.
[0004] In the existing technology, the slurry used for grouting sanitary ceramics mainly uses potassium and sodium feldspar as flux raw materials. However, since potassium and sodium feldspar are high-temperature elements in ceramic firing temperature, it is difficult to achieve low-temperature rapid firing of sanitary ceramic blanks. Summary of the Invention
[0005] The purpose of this invention is to propose a low-temperature rapid-firing slurry containing lithium tailings and its high-pressure grouting products for ceramic sanitary ware. By introducing lithium tailings to optimize the raw material formula of the slurry, the low-temperature rapid firing of sanitary ceramic blanks is achieved, which greatly reduces the production cost of sanitary ceramic products and improves the production efficiency of sanitary ceramic products, thereby overcoming the shortcomings of the prior art.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] According to the mass fractions, a low-temperature rapid-burning mud containing lithium tailings includes the following raw materials: 10-20 parts lithium tailings, 10-20 parts kaolin, 10-20 parts porcelain stone, 10-20 parts kaolin, 10-20 parts sericite clay, 0-10 parts black mud, 0-5 parts wollastonite, 0-5 parts magnesia, 0-10 parts potassium feldspar, and 5-15 parts high-temperature sand.
[0008] The melting temperature of the high-temperature sand is 1250–1300°C.
[0009] Preferably, the Li2O content of the lithium tailings is 0.2-3% by mass percentage.
[0010] Preferably, the lithium tailings, by mass percentage, comprise the following chemical composition: SiO2 65-75%, Al2O3 15-25%, Fe2O3 0-0.5%, TiO2 0-0.1%, CaO 0-1%, MgO 0-1%, K2O 1-5%, Na2O 1-10%, and Li2O 0.2-3%, with the remainder being loss on ignition.
[0011] Preferably, the lithium tailings, by mass percentage, comprise the following chemical composition: SiO2 69.56%, Al2O3 18.7%, Fe2O3 0.48%, TiO2 0.06%, CaO 0.88%, MgO 0.21%, K2O 2.72%, Na2O 4.22%, and Li2O 0.27%, with the remainder being loss on ignition.
[0012] Preferably, the lithium tailings have a particle size ≤ 0.6 mm.
[0013] Preferably, the magnesia clay comprises the following chemical components by mass percentage: 62.12% SiO2, 0.36% Al2O3, 0.83% Fe2O3, 0.01% TiO2, 0.42% CaO, 30.75% MgO, 0.20% K2O, and 0.12% Na2O, with the remainder being loss on ignition.
[0014] Preferably, the high-temperature sand comprises the following chemical components by mass percentage: SiO2 69.67%, Al2O3 20.04%, Fe2O3 0.76%, TiO2 0.13%, CaO 0.62%, MgO 0.02%, K2O 2.73%, and Na2O 0.61%, with the remainder being loss on ignition.
[0015] Preferably, the kaolin, by mass percentage, comprises the following chemical composition: SiO2 70.18%, Al2O3 18.19%, Fe2O3 0.49%, TiO2 0.01%, CaO 0.52%, MgO 0.01%, K2O 4.73%, and Na2O 0.86%, with the remainder being loss on ignition;
[0016] According to mass percentage, the sericite clay material comprises the following chemical components: SiO2 67.52%, Al2O3 22.28%, Fe2O3 0.14%, TiO2 0.02%, CaO 0.13%, MgO 0.01%, K2O 4.53%, and Na2O 1.23%, with the remainder being loss on ignition;
[0017] The black mud comprises the following chemical components by mass percentage: SiO2 55.09%, Al2O3 27.39%, Fe2O3 1.40%, TiO2 0.05%, CaO 0.30%, MgO 0.01%, K2O 1.76%, and Na2O 0.61%, with the remainder being loss on ignition.
[0018] According to the mass fractions, a low-temperature rapid-burning mud containing lithium tailings includes the following raw materials: 15 parts lithium tailings, 15 parts kaolin, 15 parts porcelain stone, 15 parts kaolin, 15 parts sericite clay, 10 parts black mud, 2 parts wollastonite, 5 parts magnesia, and 8 parts high-temperature sand.
[0019] A ceramic sanitary ware high-pressure grouting product is prepared using the above-mentioned low-temperature fast-firing slurry containing lithium tailings. The firing temperature of the ceramic sanitary ware high-pressure grouting product is 1215-1225℃, and the firing cycle is 14-16h.
[0020] The technical solution provided by this invention may include the following beneficial effects:
[0021] 1. This solution introduces industrial waste lithium tailings into the slurry formulation to replace the conventional high-temperature material potassium-sodium feldspar in existing technologies. This lowers the firing temperature while ensuring fluxing effect, enabling low-temperature rapid firing of high-pressure grouting products and improving the production efficiency of sanitary ware ceramics. Simultaneously, the shrinkage and water absorption rates of the fired products meet production targets. Furthermore, this solution adds inexpensive magnesia clay to the slurry formulation in conjunction with lithium tailings, further reducing the firing temperature. Moreover, due to the synergistic effect of magnesia clay and lithium tailings, the amount of high-temperature sand added to the slurry formulation is lower than in conventional formulations. This allows for a reduction in the raw proportion of mullite, thereby achieving an overall decrease in firing temperature. Additionally, since lithium tailings are industrial waste and magnesia clay is inexpensive, coupled with the reduced high-temperature sand content, the production cost of the low-temperature rapid-firing slurry is significantly reduced, effectively lowering the cost of sanitary ware ceramic products.
[0022] 2. In order to avoid deformation of the green body and affect the matching of the green body and glaze of the high-pressure grouting ceramic sanitary ware products, the amount of lithium tailings and magnesia added to the low-temperature fast-firing slurry was also limited, thereby adjusting the expansion coefficient of the slurry to stabilize the firing quality of the green body. Detailed Implementation
[0023] A low-temperature rapid-burning slurry containing lithium tailings comprises the following raw materials in parts by weight: 10-20 parts lithium tailings, 10-20 parts kaolin, 10-20 parts porcelain stone, 10-20 parts kaolin, 10-20 parts sericite clay, 0-10 parts black mud, 0-5 parts wollastonite, 0-5 parts magnesia, 0-10 parts potassium feldspar, and 5-15 parts high-temperature sand.
[0024] The melting temperature of the high-temperature sand is 1250–1300°C.
[0025] In the existing technology, the slurry used for grouting sanitary ceramics mainly uses potassium and sodium feldspar as flux raw materials. However, since potassium and sodium feldspar are high-temperature elements in ceramic firing temperature, it is difficult to achieve low-temperature rapid firing of sanitary ceramic blanks.
[0026] To achieve low-temperature rapid firing of sanitary ceramic blanks, this technical solution proposes a low-temperature rapid firing slurry suitable for high-pressure grouting of sanitary ceramic products. By introducing lithium tailings to optimize the raw material formula of the slurry, it is beneficial to reduce the production cost of sanitary ceramic products and improve the production efficiency of sanitary ceramic products.
[0027] Specifically, this solution introduces industrial waste lithium tailings into the slurry formulation to replace the conventional high-temperature material potassium-sodium feldspar in existing technologies. This lowers the firing temperature while ensuring fluxing effects, enabling low-temperature rapid firing of high-pressure grouting products and improving the production efficiency of sanitary ware ceramics. Simultaneously, the shrinkage and water absorption rates of the fired products meet production targets. Furthermore, this solution adds inexpensive magnesia clay to the slurry formulation in conjunction with lithium tailings, further reducing the firing temperature. Moreover, due to the synergistic effect of magnesia clay and lithium tailings, the amount of high-temperature sand added to the slurry formulation is lower than in conventional formulations. This allows for a reduction in the raw proportion of mullite, thereby achieving an overall decrease in firing temperature. Additionally, since lithium tailings are industrial waste and magnesia clay is inexpensive, coupled with the reduced high-temperature sand content, the production cost of the low-temperature rapid-firing slurry is significantly reduced, effectively lowering the cost of sanitary ware ceramic products.
[0028] More specifically, the addition of lithium tailings in the formula is also beneficial to increase the grouting thickness of the product during high-pressure grouting, thereby improving grouting efficiency by reducing grouting time. However, in order to avoid deformation of the green body and affect the matching of the green body and glaze of the high-pressure grouting ceramic sanitary products, this solution needs to limit the amount of lithium tailings and magnesia added to the low-temperature fast-firing slurry, thereby adjusting the expansion coefficient of the slurry to stabilize the firing quality of the green body.
[0029] To further clarify, the Li2O content of the lithium tailings is 0.2-3% by mass percentage.
[0030] In a preferred embodiment of this technical solution, using the Li2O content of lithium tailings as a material selection criterion is more conducive to ensuring its fluxing effect.
[0031] To further clarify, the lithium tailings, by mass percentage, comprise the following chemical composition: SiO2 65–75%, Al2O3 15–25%, Fe2O3 0–0.5%, TiO2 0–0.1%, CaO 0–1%, MgO 0–1%, K2O 1–5%, Na2O 1–10%, and Li2O 0.2–3%, with the remainder being loss on ignition.
[0032] To further clarify, the lithium tailings, by mass percentage, comprise the following chemical composition: 69.56% SiO2, 18.7% Al2O3, 0.48% Fe2O3, 0.06% TiO2, 0.88% CaO, 0.21% MgO, 2.72% K2O, 4.22% Na2O, and 0.27% Li2O, with the remainder being loss on ignition.
[0033] To further clarify, the particle size of the lithium tailings is ≤0.6mm.
[0034] In another preferred embodiment of this technical solution, the particle size of lithium tailings is further optimized. Lithium tailings with the above-mentioned particle size are easier to ball mill, and the particles are fine. During ball milling, the particle size distribution moves from 30μm to 20μm, increasing the number of larger particles in the middle and reducing the number of coarse particles. This can effectively improve the movement displacement of particles when they are pushed by pressure during high-pressure grouting.
[0035] To further clarify, the magnesian clay comprises the following chemical components by mass percentage: 62.12% SiO2, 0.36% Al2O3, 0.83% Fe2O3, 0.01% TiO2, 0.42% CaO, 0.75% MgO, 0.20% K2O, and 0.12% Na2O, with the remainder being loss on ignition.
[0036] The magnesia clay added in this scheme has an MgO content as high as 30%, which can more effectively cooperate with lithium tailings to achieve low-temperature rapid firing.
[0037] To further clarify, the high-temperature sand comprises the following chemical components by mass percentage: 69.67% SiO2, 20.04% Al2O3, 0.76% Fe2O3, 0.13% TiO2, 0.62% CaO, 0.02% MgO, 2.73% K2O, and 0.61% Na2O, with the remainder being loss on ignition.
[0038] To further clarify, the kaolin, by mass percentage, comprises the following chemical components: SiO2 70.18%, Al2O3 18.19%, Fe2O3 0.49%, TiO2 0.01%, CaO 0.52%, MgO 0.01%, K2O 4.73%, and Na2O 0.86%, with the remainder being loss on ignition.
[0039] According to mass percentage, the sericite clay material comprises the following chemical components: SiO2 67.52%, Al2O3 22.28%, Fe2O3 0.14%, TiO2 0.02%, CaO 0.13%, MgO 0.01%, K2O 4.53%, and Na2O 1.23%, with the remainder being loss on ignition;
[0040] The black mud comprises the following chemical components by mass percentage: SiO2 55.09%, Al2O3 27.39%, Fe2O3 1.40%, TiO2 0.05%, CaO 0.30%, MgO 0.01%, K2O 1.76%, and Na2O 0.61%, with the remainder being loss on ignition.
[0041] To further explain, according to the mass fractions, the low-temperature rapid-burning mud containing lithium tailings includes the following raw materials: 15 parts lithium tailings, 15 parts kaolin, 15 parts porcelain stone, 15 parts kaolin, 15 parts sericite clay, 10 parts black mud, 2 parts wollastonite, 5 parts magnesia, and 8 parts high-temperature sand.
[0042] This technical solution also provides an optimal formula for low-temperature rapid-fired slurry containing lithium tailings, which can achieve a slurry thickness of 7.3 mm / 45 min. Under firing conditions of 1215–1225 °C and 14–16 h, the shrinkage rate and water absorption rate of the green body product can meet the production requirements.
[0043] A ceramic sanitary ware high-pressure grouting product is prepared using the above-mentioned low-temperature fast-firing slurry containing lithium tailings. The firing temperature of the ceramic sanitary ware high-pressure grouting product is 1215-1225℃, and the firing cycle is 14-16h.
[0044] Using the slurry formula in this scheme to prepare high-pressure grouting ceramic sanitary ware products is beneficial for achieving low-temperature rapid firing of sanitary ware ceramic blanks, thereby improving the production efficiency of sanitary ware ceramic products.
[0045] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0046] Example group
[0047] High-pressure grouting was performed on the low-temperature rapid-fired slurry containing lithium tailings according to the raw material formula in Table 1, and the slurry absorption thickness of each embodiment was tested. The ceramic sanitary ware high-pressure grouting products were obtained by firing under the firing conditions in Table 2, and the shrinkage rate and water absorption rate of the ceramic sanitary ware high-pressure grouting products of each embodiment were tested according to the conventional shrinkage rate and water absorption rate tests in the sanitary ware ceramics field. The results are shown in Table 3 below.
[0048] Table 1 Raw material formulation for low-temperature rapid-burning slurry containing lithium tailings
[0049] Ingredients (portions) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 lithium tailings 5 10 15 15 15 15 porcelain clay 15 15 15 15 15 15 porcelain stone 15 15 15 15 15 15 Kaolin 15 15 15 15 15 15 Sericite clay material 15 15 15 15 15 15 Black mud 10 10 10 10 10 10 Wollastonite 2 2 2 2 2 2 Magnesia soil 3 3 3 5 5 5 Potassium sodium feldspar 10 5 0 0 0 0 high temperature sand 10 10 10 8 8 8
[0050] in:
[0051] The lithium tailings, by mass percentage, comprise the following chemical composition: SiO2 69.56%, Al2O3 18.7%, Fe2O3 0.48%, TiO2 0.06%, CaO 0.88%, MgO 0.21%, K2O 2.72%, Na2O 4.22%, and Li2O 0.27%, with the remainder being loss on ignition.
[0052] According to mass percentage, magnesian clay comprises the following chemical components: SiO2 62.12%, Al2O3 0.36%, Fe2O3 0.83%, TiO2 0.01%, CaO 0.42%, MgO 30.75%, K2O 0.20%, and Na2O 0.12%, with the remainder being loss on ignition.
[0053] According to mass percentage, the high-temperature sand contains the following chemical components: SiO2 69.67%, Al2O3 20.04%, Fe2O3 0.76%, TiO2 0.13%, CaO 0.62%, MgO 0.02%, K2O 2.73%, and Na2O 0.61%, with the remainder being loss on ignition.
[0054] According to mass percentage, the kaolin comprises the following chemical components: SiO2 70.18%, Al2O3 18.19%, Fe2O3 0.49%, TiO2 0.01%, CaO 0.52%, MgO 0.01%, K2O 4.73%, and Na2O 0.86%, with the remainder being loss on ignition;
[0055] According to mass percentage, the sericite clay material comprises the following chemical components: SiO2 67.52%, Al2O3 22.28%, Fe2O3 0.14%, TiO2 0.02%, CaO 0.13%, MgO 0.01%, K2O 4.53%, and Na2O 1.23%, with the remainder being loss on ignition;
[0056] According to mass percentage, the black mud includes the following chemical components: SiO2 55.09%, Al2O3 27.39%, Fe2O3 1.40%, TiO2 0.05%, CaO 0.30%, MgO 0.01%, K2O 1.76%, and Na2O 0.61%, with the remainder being loss on ignition.
[0057] Table 2. Firing conditions for low-temperature rapid-fired slurry from lithium-containing tailings.
[0058]
[0059] Table 3. Test Items for Low-Temperature Rapid-Firing Slurry and High-Pressure Grouting Products of Lithium-Containing Tailings
[0060]
[0061] As can be seen from the test results in Table 3, this scheme optimizes the raw material formula of the mud by introducing lithium tailings, which can effectively achieve low-temperature rapid firing of sanitary ceramic blanks, greatly reduce the production cost of sanitary ceramic products, and improve the production efficiency of sanitary ceramic products, thus overcoming the shortcomings of the existing technology.
[0062] The technical principles of the present invention have been described above with reference to specific embodiments. These descriptions are merely for explaining the principles of the invention and should not be construed as limiting the scope of protection of the invention in any way. Based on this explanation, those skilled in the art can readily conceive of other specific embodiments of the invention without inventive effort, and these embodiments will all fall within the scope of protection of the present invention.
Claims
1. A low-temperature rapid-burning slurry for lithium-containing tailings, characterized in that, Used in the preparation of high-pressure grouting products for ceramic sanitary ware; According to the mass fractions, the low-temperature rapid-burning slurry comprises the following raw materials: 10-20 parts lithium tailings, 10-20 parts kaolin, 10-20 parts porcelain stone, 10-20 parts kaolin, 10-20 parts sericite clay, 10 parts black mud, 2 parts wollastonite, 3 or 5 parts magnesia, 0-10 parts potassium-sodium feldspar, and 5-15 parts high-temperature sand. The melting temperature of the high-temperature sand is 1250–1300°C; The high-temperature sand comprises the following chemical components by mass percentage: SiO2 69.67%, Al2O3 20.04%, Fe2O3 0.76%, TiO2 0.13%, CaO 0.62%, MgO 0.02%, K2O 2.73%, and Na2O 0.61%, with the remainder being loss on ignition.
2. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 1, characterized in that, The lithium tailings contain 0.2-3% Li2O by mass percentage.
3. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 2, characterized in that, The lithium tailings, by mass percentage, comprise the following chemical components: SiO2 65–75%, Al2O3 15–25%, Fe2O3 0–0.5%, TiO2 0–0.1%, CaO 0–1%, MgO 0–1%, K2O 1–5%, Na2O 1–10%, and Li2O 0.2–3%, with the remainder being loss on ignition.
4. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 3, characterized in that, The lithium tailings, by mass percentage, comprise the following chemical composition: SiO2 69.56%, Al2O3 18.7%, Fe2O3 0.48%, TiO2 0.06%, CaO 0.88%, MgO 0.21%, K2O 2.72%, Na2O 4.22%, and Li2O 0.27%, with the remainder being loss on ignition.
5. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 1, characterized in that, The lithium tailings have a particle size ≤ 0.6 mm.
6. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 1, characterized in that, The magnesian clay comprises the following chemical components by mass percentage: SiO2 62.12%, Al2O3 0.36%, Fe2O3 0.83%, TiO2 0.01%, CaO 0.42%, MgO 30.75%, K2O 0.20%, and Na2O 0.12%, with the remainder being loss on ignition.
7. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 1, characterized in that, According to mass percentage, the kaolin comprises the following chemical components: SiO2 70.18%, Al2O3 18.19%, Fe2O3 0.49%, TiO2 0.01%, CaO 0.52%, MgO 0.01%, K2O 4.73%, and Na2O 0.86%, with the remainder being loss on ignition; According to mass percentage, the sericite clay material comprises the following chemical components: SiO2 67.52%, Al2O3 22.28%, Fe2O3 0.14%, TiO2 0.02%, CaO 0.13%, MgO 0.01%, K2O 4.53%, and Na2O 1.23%, with the remainder being loss on ignition; The black mud comprises the following chemical components by mass percentage: SiO2 55.09%, Al2O3 27.39%, Fe2O3 1.40%, TiO2 0.05%, CaO 0.30%, MgO 0.01%, K2O 1.76%, and Na2O 0.61%, with the remainder being loss on ignition.
8. The low-temperature rapid-burning slurry for lithium-containing tailings according to claim 1, characterized in that, According to the mass fractions, the raw materials include the following: 15 parts lithium tailings, 15 parts kaolin, 15 parts porcelain stone, 15 parts kaolin, 15 parts sericite clay, 10 parts black mud, 2 parts wollastonite, 5 parts magnesia, and 8 parts high-temperature sand.
9. A high-pressure grouting product for ceramic sanitary ware, characterized in that, The ceramic sanitary ware high-pressure injection product is prepared using low-temperature rapid-firing slurry of lithium-containing tailings as described in any one of claims 1 to 8, and the firing temperature is 1215 to 1225°C, with a firing cycle of 14 to 16 hours.
Citation Information
Patent Citations
Firing method of low-temperature fast-fired glazed tile and low-temperature fast-fired glazed tile
CN111548138A
High-plasticity and high-water-permeability high-pressure grouting slurry and preparation method thereof
CN115159955A
Ceramic green body, ceramic tile and preparation method of ceramic green body
CN115893978A
